2019
DOI: 10.1016/j.bcab.2019.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Antiurolithic activity and biotransformation of galloylquinic acids by Aspergillus alliaceus ATCC10060, Aspergillus brasiliensis ATCC 16404, and Cunninghamella elegans ATCC 10028b

Abstract: Copaifera lucens n-butanolic fraction (BF) was used as a source of galloylquinic acids, and aerobically incubated with Aspergillus alliaceus ATCC10060, Aspergillus brasiliensis ATCC 16404, and Cunninghamella elegans ATCC 10028b cultures for 60 and 120 h. Out of the three studied filamentous fungi, A. alliaceus ATCC10060 was able to degrade galloylquinic acids into one major metabolite, 3-O-methylgallic acid (M1). The product was identified by 1 H-NMR, UPLC-MS/MS and its potential effect on calcium oxalate mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Another study stated that C. glabrata was susceptible to the leaf extract of Camellia sinensis , which is rich in polyphenolic compounds ( 20 ). Other studies mentioned that plant polyphenol-rich extracts had potential activity against pathogenic fungi ( 21 , 22 ), consistent with the polyphenolic properties of GQAs, which are capable of reducing reactive oxygen species due to their promising antioxidant properties ( 16 , 17 ). Additionally, our tested compounds showed a wider safe window in an MTT cytotoxicity assay using Vero cells, with an IC 50 of 168.17 mg/mL.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Another study stated that C. glabrata was susceptible to the leaf extract of Camellia sinensis , which is rich in polyphenolic compounds ( 20 ). Other studies mentioned that plant polyphenol-rich extracts had potential activity against pathogenic fungi ( 21 , 22 ), consistent with the polyphenolic properties of GQAs, which are capable of reducing reactive oxygen species due to their promising antioxidant properties ( 16 , 17 ). Additionally, our tested compounds showed a wider safe window in an MTT cytotoxicity assay using Vero cells, with an IC 50 of 168.17 mg/mL.…”
Section: Discussionsupporting
confidence: 57%
“…A voucher sample was kept (RB 474303) as a reference at the Laboratory of Pharmacognosy, FCFRP, Brazil. The major galloylquinic acid compounds (GQAs) were extracted and identified spectrophotometrically in the n -butanolic fraction of C. lucens , using high-performance liquid chromatography (HPLC), based on their characteristic UV spectra according to our previously reported data ( 16 , 17 ). The compounds were prepared as a stock solution (50 mg/mL) in dimethyl sulfoxide (DMSO) and stored at −80°C until use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexin A1 that is highly expressed in epithelial cells of polyps can bind COM crystal in the urine to the surface of calculi through its transmembrane domain. [ 18 , 19 ] Alternatively, it can bind oxalic acid and calcium ions in the urine through its target protein S100 A9, which may be realized by EF-hand motifs in the S100 A9 domain. [ 4 , 20 ] In our study, correlation analysis of the H-score of annexin A1/S100 A9 indicated a strong correlation between the expressions of the 2 proteins; this suggested a synergistic relationship between annexin A1 and S100 A9 in binding COM crystal.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of GFP‐Fgatg8 in F. graminearum could be measured by Western blot analysis (El‐Salam et al., 2019). Twenty microlitres of protein sample was loaded into the stacking gel, and the voltage was kept at 100 V. Then, the voltage was increased to 130 V when the sample ran into the separating gel.…”
Section: Methodsmentioning
confidence: 99%